2017
DOI: 10.1111/mmi.13669
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered control of peroxisomal activity upon salt stress in Saccharomyces cerevisiae

Abstract: Peroxisomes are dynamic organelles and the sole location for fatty acid β-oxidation in yeast cells. Here, we report that peroxisomal function is crucial for the adaptation to salt stress, especially upon sugar limitation. Upon stress, multiple layers of control regulate the activity and the number of peroxisomes. Activated Hog1 MAP kinase triggers the induction of genes encoding enzymes for fatty acid activation, peroxisomal import and β-oxidation through the Adr1 transcriptional activator, which transiently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…For example, the Myb-like HTH transcription factor Dot6 in Candida albicans was reported to be involved in the TOR signaling pathway (Chaillot et al 2019), which was regulated in the responses to cell wall damaging stress in F. graminearum (Gu et al 2015). Hap2/5, CRZ1, ADR1, MIG1/2/3, MSN2/4, and RDS2 have been reported to function directly in cell wall integrity or osmotic stress (Proft and Serrano 1999;Mendizabal et al 2001;Wong et al 2003;Panadero et al 2007;Moreno et al 2008;Nino-Vega et al 2009;Liu et al 2013;Thewes 2014;Manzanares-Estreder et al 2017;Jung et al 2018;Miller et al 2019). Combined with previous Table 5 Differential functional binding sites predicted in the non-coding region upstream of CYP51 in U. virens with 'CC' insertion mutations (sequence B) relative to that without 'CC' insertion (sequence A) using the JASPAR database studies showing that the CYP51 gene encodes an enzyme that is part of the cell membrane, the current predictions further suggested that the resistance of U. virens to DMI fungicides may be related to CYP51 overexpression mediated by 'CC' insertion mutations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Myb-like HTH transcription factor Dot6 in Candida albicans was reported to be involved in the TOR signaling pathway (Chaillot et al 2019), which was regulated in the responses to cell wall damaging stress in F. graminearum (Gu et al 2015). Hap2/5, CRZ1, ADR1, MIG1/2/3, MSN2/4, and RDS2 have been reported to function directly in cell wall integrity or osmotic stress (Proft and Serrano 1999;Mendizabal et al 2001;Wong et al 2003;Panadero et al 2007;Moreno et al 2008;Nino-Vega et al 2009;Liu et al 2013;Thewes 2014;Manzanares-Estreder et al 2017;Jung et al 2018;Miller et al 2019). Combined with previous Table 5 Differential functional binding sites predicted in the non-coding region upstream of CYP51 in U. virens with 'CC' insertion mutations (sequence B) relative to that without 'CC' insertion (sequence A) using the JASPAR database studies showing that the CYP51 gene encodes an enzyme that is part of the cell membrane, the current predictions further suggested that the resistance of U. virens to DMI fungicides may be related to CYP51 overexpression mediated by 'CC' insertion mutations.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the autophagic removal of damaged peroxisomes with increased ROS production could be an important mechanism to maintain a correct redox balance in the cell [ 172 ]. Consistent with this idea is the finding that peroxisomal proliferation seems to be regulated by the redox state of the organelle [ 19 ] and that abiotic stress such as salt stress induces the number of peroxisomes via Dnm1 and Vps1 [ 186 ].…”
Section: Quality Control Of Peroxisomes and Mitochondria By Autophmentioning
confidence: 92%
“…Additionally, the mitochondria peroxisome interaction might be regulated dynamically to modulate ROS homeostasis, the interchange of metabolites or the respiratory efficiency. In this respect, it has been recently shown that the number of peroxisomes attached to the mitochondrial network increases upon cellular stress such as high salinity, which is known to also increase cellular ROS levels [ 186 ].…”
Section: Physiological and Physical Interaction Of Peroxisomes Andmentioning
confidence: 99%
“…Peroxisomal activity is important for the successful adaptation to high salinity, which becomes even more evident upon sugar limitation. The HOG pathway controls the transcriptional up-regulation of numerous genes involved in the activation of fatty acids from internal lipid stores, their internalization and β-oxidation in peroxisomes and their conversion into acetyl-carnitine (Manzanares-Estreder et al 2017). The transcription factor in charge of this switch is Adr1, which was previously known to be regulated during the transition from fermentation to respiration via the Snf1 kinase (Ratnakumar and Young 2010).…”
mentioning
confidence: 99%
“…Peroxisomal adaptation to salt stress is also microscopically evident, since the number of the organelle quickly increases upon exposure to high salinity. The dynamin related GTPases Dnm1 and Vps1 are involved in this stress-stimulated process, which depends on retrograde signaling but not the HOG pathway (Manzanares-Estreder et al 2017). Overall, a yeast cell which actively combats a salinity insult, roughly doubles the number of peroxisomes attached to the mitochondrial network, and peroxisomal activity is actually needed to induce mitochondrial respiration under these conditions.…”
mentioning
confidence: 99%